Determinants of the Evolution of the South Korean Luxury Fashion Market - Kim, Ga Hyun; Šváb, Patrik; Horáková, Ludmila; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis will examine the evolution of the South Korean luxury fashion market by analyzing key macroeconomic indicators and significant events in the country's history that have shaped the market into its current state. South Korea is one of the largest consumers of luxury fashion in the world; however, it is currently under-researched in this sector. The thesis will therefore also focus on the socioeconomic aspects that have influenced the demand for luxury goods in this country. Lastly, it will discuss the market's current most pressing issues and potential further development with the onset of digitalization.
Vedoucí práce: Patrik Šváb
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses